Journal of the Australian Mathematical Society - Australian Mathematical Society (Canberra, Australia : Australian Mathematical Society, 2001)
Access available online from 1969-
Keywords: Mathematics -- Periodicals; Statistics -- Periodicals; Mathematical statistics -- Periodicals; Wiskunde